Patient considerations and clinical utility of a fixed dose combination of saxagliptin/metformin in the treatment of type 2 diabetes - Derosa, Giuseppe (Dove Medical Press, 2011)
INTRODUCTION: Targeting glycated hemoglobin (HbA(1c)) levels below 7.0% is considered a primary goal of diabetes care, given its importance in obtaining a sustained reduction in microvascular, and possibly macrovascular complications. AIM: The aim of this review was to evaluate the clinical utility of a fixed dose combination of saxagliptin/metformin in the treatment of type 2 diabetes. EVIDENCE REVIEW: The combination of saxagliptin/metformin was well tolerated and produced sustained glycemic control for up to 76 weeks, with greater improvements in glycemic parameters compared with either drug alone. The saxagliptin/metformin combination also proved its non-inferiority compared with either sulfonylurea/metformin or sitagliptin/metformin combinations. PLACE IN THERAPY: Clinical practice recommends lifestyle interventions together with starting metformin at the time that the type 2 diabetes mellitus is diagnosed. Once metformin fails to maintain glycemic control, the addition of DPP-4 inhibitors should be the logical choice because of their effects on HbA(1c) compared to the addition of a sulfonylurea or glitazone, and because of their positive effects on beta cell function and their neutral effects on body weight. Furthermore, DPP-4 inhibitors prevent the risk of hypoglycemia posed by sulfonylureas.